2018
DOI: 10.4258/hir.2018.24.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Automated Audiometry: A Review of the Implementation and Evaluation Methods

Abstract: ObjectivesAutomated audiometry provides an opportunity to do audiometry when there is no direct access to a clinical audiologist. This approach will help to use hearing services and resources efficiently. The purpose of this study was to review studies related to automated audiometry by focusing on the implementation of an audiometer, the use of transducers and evaluation methods.MethodsThis review study was conducted in 2017. The papers related to the design and implementation of automated audiometry were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…Headphones differ in frequency characteristics depending on their specific details of construction. Thus, the use of different types of headphones (circumaural, supra-aural, earbud, or insert headphones) can lead to large variations in amplitude of the test signal depending on their frequency response (Shojaeemend and Ayatollahi, 2018). Consequently, inaccuracies introduced by using non-standardized headphones, frequently applied in consumer products, can be resolved by applying calibrated, professional headphones designed for audiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Headphones differ in frequency characteristics depending on their specific details of construction. Thus, the use of different types of headphones (circumaural, supra-aural, earbud, or insert headphones) can lead to large variations in amplitude of the test signal depending on their frequency response (Shojaeemend and Ayatollahi, 2018). Consequently, inaccuracies introduced by using non-standardized headphones, frequently applied in consumer products, can be resolved by applying calibrated, professional headphones designed for audiometry.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, Mahomed et al (21) suggested that automated pure-tone audiometry provides an accurate measure, but validation is still needed for specific cases such as difficult-to-test populations. In a more recent review, Shojaeemend and Ayatollahi (22) concluded that automated audiometry produces clinically acceptable results compared with traditional audiometry.…”
Section: Previous Researchmentioning
confidence: 99%
“…Hearing loss is a partial or complete inability to hear in one or both ears 60 and can be accompanied by tinnitus or (hissing noise or high‐pitched ringing in the ears when sound is not present), tympanophonia (or autophonia, abnormal hearing of one's own voice), hyperacusis (sensitivity, pain), and vertigo (problems with equilibrium) 61 . Tests for hearing loss measure hearing sensitivity via an audiogram, which is a graph of individual audible thresholds (intensity and frequency of a given tone) plotted against a standard curve 62 . The clinical definition of normal hearing sensitivity is 25 dB or better in both ears, with impaired hearing sensitivity defined as mild (26–40 dB higher than normal), moderate (41–60 dB higher than normal), severe (61–80 dB higher than normal), and profound (81 dB or greater) 60 .…”
Section: Auditionmentioning
confidence: 99%